Medusae from Mcmurdo Sound, Ross Sea including the descriptions of two new species, Leuckartiara brownei and Benthocodon hyalinus - Larson, R.; Harbison, G. (Polar Biology, 1990)
Seven species of medusae were collected using scuba equipment in neritic waters of McMurdo Sound, Ross Sea, Antarctica. Two species dominated, the narcomedusa Solmundella bitentaculata and the scyphomedusa Diplulmaris antarctica. Two new taxa were found. Leuckartiara brownei n. sp., a pandeid anthomedusa, has gondas with two major longitudinal folds in the interradii and several smaller perradially directed folds. Besides four large perradial tentacles, it has up to 28 short "rudimentary" tentacles. This is the first report of this genus from the Southern Ocean. BENTHOCODON hyalinus n. gen., n. sp., a rhopalonematoid trachymedusa, has 8 linear to sinuous gonads on the radial canals. The tubular manubrium is attached to a gastric peduncle. The tentacles are numerous (about 800) and grow successively. This is the second reported trachymedusa from the Ross Sea. Solmudella bitentaculata ate the thecosome pteropod Limacina helicina. Diplu maris antarctica medusae fed on the gymnosome pteropod Clione antarctica and on L. helicina. The hyperiid amphipod Hyperiella dilatata, mostly females, was seen attached to the exumbrellas of both D. antarctica and S. bitentaculata. Up to 54 amphipods were seen on each D. antarctica medusa. The amphipods did no visible damage to the medusae.
published December 1990